Interacting effects of landscape context and habitat quality on flower visiting insects in agricultural landscapes - Kleijn, David; van Langevelde, Frank (Basic and applied ecology, 2006)
Landscape context and habitat quality may have pronounced effects on the diversity of flower visiting insects. We investigated whether the effects of landscape context and habitat quality on flower visiting insects interact in agricultural landscapes in the Netherlands. Landscape context was expressed as the area of semi-natural habitats or the density of linear landscape features, and was quantified at spatial scales ranging from 250 to 2000 m. Habitat quality was determined as flower abundance. Species richness and abundance of hoverflies and bees were determined along 16 stream banks experiencing similar environmental conditions but situated in areas with contrasting landscape context. Only flower abundance and the area of semi-natural habitats within 500–1000 m were significantly related to species richness of hoverflies and bees and these factors had interacting effects on both species groups. Our results suggest that the regional area of semi-natural habitats had a positive effect on hoverfly species richness when flower abundance was relatively high, but not when flower abundance was low. Moreover, flower abundance had positive effects on hoverfly species richness only in areas with relatively many semi-natural habitats. Contrastingly, flower abundance had a more positive effect on bee species richness in landscapes with few semi-natural habitats compared to landscapes with more semi-natural habitats. Our results suggest that the importance of landscape context for the species richness of flower visiting insects depends upon the quality of the habitat patches. Landschaftseinbindung und Habitatqualität könnten deutliche Auswirkungen auf die Diversität blütenbesuchender Insekten haben. Wir untersuchten, ob die Auswirkungen der Landschaftseinbindung und der Habitatqualität auf blütenbesuchende Insekten in Agrarlandschaften in den Niederlanden interagieren. Die Landschaftseinbindung wurde durch die Fläche der halbnatürlichen Habitate oder die Dichte linienhafter Landschaftsstrukturen ausgedrückt und auf räumlichen Skalen quantifiziert, die von 250 m bis 2000 m reichten. Die Habitatqualität wurde als Blütenabundanz bestimmt. Es wurde der Artenreichtum und die Abundanz von Schwebfliegen und Bienen entlang von Flussufern bestimmt, die gleiche Umweltbedingungen aufwiesen, sich aber in Gebieten unterschiedlicher Landschaftseinbindung befanden. Nur die Blütenabundanz und die Fläche halbnatürlicher Habitate innerhalb von 500–1000 m war signifikant mit dem Artenreichtum der Schwebfliegen und Bienen verbunden und die Faktoren hatten interagierende Auswirkungen auf beide Artengruppen. Unsere Ergebnisse weisen darauf hin, dass die regionale Fläche der halbnatürlichen Habitate einen positiven Effekt auf den Artenreichtum der Schwebfliegen hat, wenn die Blütenabundanz relativ hoch ist, jedoch nicht, wenn die Blütenabundanz gering ist. Darüber hinaus hatte die Blütenabundanz nur in Gebieten mit relativ vielen halbnatürlichen Habitaten positive Auswirkungen auf den Artenreichtum der Schwebfliegen. Im Gegensatz dazu hatte die Blütenabundanz in den Landschaften einen stärkeren positiven Effekt auf den Artenreichtum der Bienen, die im Vergleich zu Landschaften mit vielen halbnatürlichen Habitaten nur wenige halbnatürliche Habitate aufwiesen. Unsere Ergebnisse weisen darauf hin, dass die Bedeutung der Landschaftseinbindung für den Artenreichtum von blütenbesuchenden Insekten von der Qualität der Habitatflecken abhängt.